Dead things are closer than they appear - Wasley, Robin (Simon & Schuster BFYR, 2024)
High school is hard enough to survive without an apocalypse to navigate. Sid Spencer has always been the most normal girl in her abnormal hometown, a tourist trap built over one of the fault lines that seal magic away from the world. Meanwhile, all Sid has to deal with is hair-ruining humidity, painful awkwardness, being one of four Asians in town, and her friends dumping her when they started dating each other - just days after the most humiliating romantic rejection faced by anyone, ever, in all of history. Then someone kills one of the Guardians who protect the seal. The earth rips open, unleashing the magic inside. Monsters crawl from the ground, no one can enter or leave, and the man behind it all is roaming the streets with a gang of violent vigilantes. When she finds out her missing brother is involved, she joind the remaining Guardians, desperate to find him and close the fault line for good. Fighting through hordes of living corpses and uncontrollable growths of forest, Sid and the ragtag crew of would-be-heroes are the only thing standing between their town and the end of the world as they know it. Between magic, murderers, and burgeoning crushes, Sid must survive being a perfectly normal girl caught in a perfectly abnormal apocalypse. Only - how can someone so ordinary make it in such an extraordinary world?
Keywords: magia; maailmanloppu; zombit; hirviöt; tytöt; veljet; pikkukaupungit